Administrative empowerment of the women's leaderships of King Saud University and its relationship to the application of quality management - Alrasheed, Sara Tawfiq (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the degree of practice of administrative empowerment and its dimensions (granting of powers, participation in decision-making, qualification and training, work groups and teamwork, and creative behavior development) among women leaders in the departments of science and medical studies at King Saud University. Also, the to identify the level of application of quality management principles (Awareness of the concept of quality management, top management commitment to the concept of quality, continuous improvement, and effective communication) among women leaders in the departments of science and medical studies at King Saud University and the type of relationship between two concepts. The study adopted the descriptive approach with its two inputs: survey and relational. The researcher used the questionnaire as a tool for study. The study community consists of all women leaders in the departments of science and medical studies at the women campus (the university city for female students) at King Saud University. The study was applied to (180) leaders (Dean, Vice Dean, Center or unit manager). The study reached several results, most notably: 1) The degree of administrative empowerment practice among women leaders in the departments of science and medical studies at King Saud University from the point of view of the study personnel came with a medium degree, that the degree of application of quality management principles in King Saud University from the viewpoint of the study personnel came At a moderate level. 2) There is a positive (positive) relationship of statistical significance at the level of significance (α≤0.01), between the degree of practicing the dimensions of administrative empowerment. 3) The degree of applying the principles of quality management in the departments of science and medical studies at King Saud University from the viewpoint of the study individuals. In light of the results of the study, the study recommended the need of developing the organizational policies to raise the level of participation of women leaders in the departments of science and medical studies at the university in decision-making, and the necessity of rehabilitating women leaders before their assignment.
Keywords: administrative empowerment; women leaders; King Saud University; application of quality management principles